Damage index estimation by analysis of meteorological disasters on - Ryu, Heeryong; Choi, Mankwon; Cho, Myeongwhan; Yu, Inho; Kim, Seungyu (International Journal of Agricultural and Biological Engineering, 2019)
This study focuses on the analysis of the effect of meteorological disasters on film plastic greenhouses by typhoons, heavy snow, strong wind, and heavy rain. The data of meteorological disasters from 1998 to 2015 were analyzed on provincial basis to calculate the damage rate depending on the weather cause. The cumulative damage area is 20279 hm2. The damage rates of typhoons, heavy snow, strong wind, and heavy rain are 46.4%, 47.4%, 2.5%, and 3.8%, respectively. The damage index of the greenhouse, which is the ratio of the greenhouse area to the cumulative damage area, was proposed to estimate the disaster risk for 17 administrative districts. The damage index data and the cumulative damage areas were divided using the Jenks’ Natural Breaks method. The average damage index is 0.66, and the damage indices are high in the metropolitan cities.Keywords: damage index, global warming, heavy snow, strong wind, heavy rain, protected horticulture, typhoon, vinyl houseDOI: 10.25165/j.ijabe.20191205.4493Citation: Ryu H R, Choi M K, Cho M W, Yu I H, Kim S Y. Damage index estimation by analysis of meteorological disasters on film plastic greenhouses. Int J Agric & Biol Eng, 2019; 12(5): 58–63.